2022
DOI: 10.1039/d2ce00713d
|View full text |Cite
|
Sign up to set email alerts
|

[Na4(N5)4(H2O)2]·H2O·2MeOH: a honeycomb-like sodium pentazolate framework with helical chains

Yuangang Xu,
Ze Xu,
Xiaopeng Zhang
et al.

Abstract: A new NaN5 framework [Na4(N5)4(H2O)2]•H2O•2MeOH was synthesized by changing the content of auxiliary ligand. It features an UNJ-type zeolite topology with double right-handed helix chains construct enclosed channels filled with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[79] Thus, considering that the left-handed helicity of the MPF-4 chains is clearly induced by coordination between Na + cations, achiral cyclo-N 5 À anions, and MSM ligands, from a macroscopic perspective, MPF-4 is characterized by an achiral framework with intrinsic left-handed homochirality. [76] They found that this compound crystallizes in a mixed solvent system of ammonia (2 M), methanol, and water. Similar to MPF-4, this framework featured a zeolitelike unj topological architecture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] Thus, considering that the left-handed helicity of the MPF-4 chains is clearly induced by coordination between Na + cations, achiral cyclo-N 5 À anions, and MSM ligands, from a macroscopic perspective, MPF-4 is characterized by an achiral framework with intrinsic left-handed homochirality. [76] They found that this compound crystallizes in a mixed solvent system of ammonia (2 M), methanol, and water. Similar to MPF-4, this framework featured a zeolitelike unj topological architecture.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, some obtained MPFs exhibited melanophlogite (MEP), chibaite (MTN), and unj zeolitic or zeolite-like topological architectures, and all three pentasil networks reported to date are sodium-or lithiumpentazolate frameworks (Figure 4). [73][74][75][76]…”
mentioning
confidence: 99%
“…16 Then in 2022, we synthesized a new UNJ-type zeolite topology with double right-handed helical chains ([Na 4 (N 5 ) 4 (H 2 O) 2 ]•H 2 -O•2MeOH). 17 As such, based on the coordination of cyclo-N 5…”
Section: Introductionmentioning
confidence: 99%
“…16 Then in 2022, we synthesized a new UNJ-type zeolite topology with double right-handed helical chains ([Na 4 (N 5 ) 4 (H 2 O) 2 ]·H 2 O·2MeOH). 17 As such, based on the coordination of cyclo -N 5 − with Na + , the introduction of auxiliary ligands will bring about the formation of NaN 5 frameworks with diverse topologies. Similarly, lithium pentazolate (LiN 5 ) is similar to sodium pentazolate, and can also form anhydrous zeolite architecture by adjusting the solvent environment of crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…), the representative of nitrogen materials, has attracted considerable research interest. [8][9][10][11][12] To isolate cyclo-N 5 − , many studies have been performed to investigate the cleavage of the C-N bond in aryl pentazoles. [13][14][15][16][17][18] In 2017, a non-metal salt and a series of metal hydrate complexes containing cyclo-N 5 − were prepared and stabilized at room temperature.…”
mentioning
confidence: 99%